The Influence Of Fee Audit, Financial Distress, And Profitability On Audit Delay In Manufacturing Company Sectors Mining Listed In Indonesian Stock Exchange 2014-2018 - Efa Castio; Erna Lovita (Indonesian Journal of Business, Accounting and Management (IJBAM), 2020)
Abstract—This study is aimed to test the effect of Fee Audit, Financial Distress and Profitability on Audit Delay in manufacturing companies in the mining sector is listed on the Indonesia Stock Exchange 2014-2018. This research uses a quantitative research approach, which is measured by using multiple linear regression based methods with the help Eviews 10. The population in this study were manufacturing companies manufacturing mining listed on the Indonesia Stock Exchange (BEI) in 2014 until 2018. The sample was determined based on purposive sampling method, with a total sample of 18 manufacturing companies manufacturing mining sectors so that the total observation in the study this is as much as 90 observation. The data used in this study are secondary data. the official website of IDX : www.idx.co.id. Bassed on partial regresson analysis, variabel that have an influence on audit delay from manufacturing companies manufacturing mining listed on the Indonesia Stock Exchange (BEI) in 2014 until 2018are financial distress, the higher the financial distress, the company will experience financial distress and then the profitability the greater profits obtained by the company, the shorter the audit report lag, because the company wants to deliver good news. The result taht has no effect on the audit delay mining company is the fee audit variabel the size of the fee given does not affect audit delay, because the auditor will always work professionally.